Zaproszenie do publikacji w piątym numerze „Tematów i Kontekstów” pt. "Polska proza nowa i najnowsza" - Pasterska, Jolanta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
This is to announce the content of the next issue of “Tematy i Konteksty”, which was given the title “The New and the Latest Polish Prose”.
Invitation to Publish in the Fifth Issue of “Tematy i Konteksty” entitled “The New and the Latest Polish Prose”
Keywords: polska proza; przemiany; tematy; prozaicy; the latest Polish prose; transformation; themes; prose writers